PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN CRITICAL THINKING DAN TANGGUNG JAWAB PADA PEMBELAJARAN IPAS KELAS IV - Suci Kodri; Syahrial Syahrial; Sukendro Sukendro (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This research aims to improve teacher activities, critical thinking skills, character of responsibility, and student learning outcomes through the application of the Discovery Learning model in the learning of science in grade IV of SD Negeri 165/IV Jambi City. The research using the Kemmis and McTaggart model methods (PTK) includes the stages of planning, implementation of actions, observation, and reflection. The subjects consisted of 18 students in grade IV. Data collection techniques use observation, tests, interviews, and documentation. The research instruments include teacher activity observation sheets, critical thinking ability observation sheets, responsibility character observation sheets, interview guidelines, and learning outcome tests that have been validated by experts. Data were analyzed using quantitative and qualitative descriptive techniques. The results of his research are that the Discovery Learning model is able to improve teacher activities, critical thinking skills, responsible character, and student learning outcomes. The increase in teacher activity can be seen in the percentage, which was originally 56% in the pre-cycle, increased by 74% in the first cycle, 88% in the second cycle, and 95% in the third cycle in the very high category. The improvement describes if the teacher gets better when carrying out the stages and managing the student-centered process. The students' critical thinking skills increased by 34% in the pre-cycle, 68% in the first cycle, 86% in the second cycle, and 94% in the third cycle. In addition, the character of student responsibility experienced a significant increase, namely 47% in the pre-cycle stage, 72% in cycle I, increased again 89% in cycle II, and reached 96% in cycle III. Not only that, the acquisition of student learning outcomes continues to increase, as reflected in the increase in the number of students who achieve learning completeness in each cycle to meet the indicators of research success. ABSTRAK Penelitian ini bertujuan untuk meningkatkan aktivitas guru, kemampuan critical thinking, karakter tanggung jawab, dan hasil belajar peserta didik melalui penerapan model Discovery Learning pada pembelajaran IPAS kelas IV SD Negeri 165/IV Kota Jambi. Penelitian menggunakan metode (PTK) model Kemmis dan McTaggart meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjeknya terdiri atas 18 peserta didik kelas IV. Teknik pengumpulan data menggunakan observasi, tes, wawancara, dan dokumentasi. Instrumen penelitian meliputi lembar observasi aktivitas guru, lembar observasi kemampuan critical thinking, lembar observasi karakter tanggung jawab, pedoman wawancara, dan tes hasil belajar yang telah divalidasi oleh ahli. Data dianalisis menggunakan teknik deskriptif kuantitatif dan kualitatif. Hasil penelitiannya model Discovery Learning mampu meningkatkan aktivitas guru, kemampuan critical thinking, karakter tanggung jawab, serta hasil belajar siswanya. Peningkatan aktivitas guru terlihat persentasenya yang semula 56% di pra siklus meningkat 74% di siklus I, 88% di siklus II, 95% di siklus III berkategori sangat tinggi. Peningkatan tersebut mendeskripsikan jika pengajar semakin baik ketika melaksanakan tahapannya dan mengelola prosesnya yang berpusat pada siswanya. Kemampuan critical thinking siswanya terjadi kenaikan 34% di pra siklus 68% di siklus I, 86% di siklus II, dan 94% di siklus III. Selain itu, karakter tanggung jawab siswanya alami kenaikan yang signifikan, yakni 47% ditahap prasiklus 72% di siklus I, meningkat lagi 89% di siklus II, dan mencapai 96% di siklus III. Tidak hanya itu, perolehan hasil belajar siswanya terus mengalami kenaikan, sebagaimana tercermin dari kenaikan jumlah siswanya yang mencapai ketuntasan belajar pada setiap siklus hingga memenuhi indikator keberhasilan penelitian.